Nanoparticle-based topical ophthalmic formulation for sustained release of stereoisomeric dipeptide prodrugs of ganciclovir. (1st September 2016) - Yang, Xiaoyan; Shah, Sujay J.; Wang, Zhiying; Agrahari, Vibhuti; Pal, Dhananjay; Mitra, Ashim K.
Abstract: Poly(d, l -lactic-co-glycolic acid) (PLGA) nanoparticles (NP) of Val-Val dipeptide monoester prodrugs of ganciclovir (GCV) including L-Val-L-Val-GCV (LLGCV), L-Val-D-Val-GCV (LDGCV) and D-Val-L-Val-GCV (DLGCV) were formulated and dispersed in thermosensitive PLGA-PEG-PLGA polymer gel for the treatment of herpes simplex virus type 1 (HSV-1)-induced viral corneal keratitis. Nanoparticles containing prodrugs of GCV were prepared by a double-emulsion solvent evaporation technique using various PLGA polymers with different drug/polymer ratios. Nanoparticles were characterized with respect to particle size, entrapment efficiency, polydispersity, drug loading, surface morphology, zeta potential and crystallinity. Prodrugs-loaded NP were incorporated into in situ gelling system. These formulations were examined for in vitro release and cytotoxicity. The results of optimized entrapment efficiencies of LLGCV-, LDGCV- and DLGCV-loaded NP are of 38.7 ± 2.0%, 41.8 ± 1.9%, and 45.3 ± 2.2%; drug loadings 3.87 ± 0.20%, 2.79 ± 0.13% and 3.02 ± 0.15%; yield 85.2 ± 3.0%, 86.9 ± 4.6% and 76.9 ± 2.1%; particle sizes 116.6 ± 4.5, 143.0 ± 3.8 and 134.1 ± 5.2 nm; and zeta potential −15.0 ± 4.96, −13.8 ± 5.26 and −13.9 ± 5.14 mV, respectively. Cytotoxicity studies suggested that all the formulations are non-toxic. In vitro release of prodrugs from NP showed a biphasic release pattern with an initial burst phase followed by a sustained phase. Such burst effect was completely eliminated when NP were suspended in thermosensitive gels with near zero-order release kinetics. Prodrugs-loaded PLGA NP dispersed in thermosensitive gels can thus serve as a promising drug delivery system for the treatment of anterior eye diseases.